State filtering for networked control systems subject to switching disturbances - Chabir, Karim; Rhouma, Taouba; Keller, Jean Yves; Sauter, Dominique (Zielona Góra: Uniwersytet Zielonogórski)
State estimation of stochastic discrete-time linear systems subject to unknown inputs has been widely studied, but few works take into account disturbances switching between unknown inputs and constant biases. We show that such disturbances affect a networked control system subject to deception attacks on the control signals transmitted by the controller to the plant via unreliable networks. This paper proposes to estimate the switching disturbance from an augmented state version of the intermittent unknown input Kalman filter. The sufficient stochastic stability conditions of the obtained filter are established when the arrival binary sequence of data losses follows a Bernoulli random process.
Keywords: Kalman filters; unknown inputs; constant bias; switching disturbances; linear systems; covariance matrix